Is fresh-frozen plasma clinically effective? An update of a systematic review of randomized controlled trials. - Yang, L; Stanworth, S; Hopewell, S; Doree, C; Murphy, M (2012)
The clinical use of frozen plasma (FP) continues to increase, both in prophylactic and in therapeutic settings. In 2004, a systematic review of all published randomized controlled trials (RCTs) revealed a lack of evidence that supported the efficacy of FP use. This is an update that includes all new RCTs published since the original review.